Secondary Neutropenias - Alister C. Ward (Biomedicines)
Neutrophils are a critical component of immunity, particularly against bacteria and other pathogens, but also in inflammation and tissue repair. As a consequence, individuals with neutropenia, defined by a reduction in absolute neutrophil counts, exhibit a strong propensity to severe infections that typically present with muted symptoms. Neutropenias encompass a heterogeneous set of disorders, comprising primary neutropenias, in which specific genes are mutated, and the more common secondary neutropenias, which have diverse non-genetic causes. These include hematological and other cancers, involving both direct effects of the cancer itself and indirect impacts via the chemotherapeutic, biological agents and cell-based approaches used for treatment. Other significant causes of secondary neutropenias are non-chemotherapeutic drugs, autoimmune and other immune diseases, infections and nutrient deficiencies. These collectively act by impacting neutrophil production in the bone marrow and/or destruction throughout the body. This review describes the biological and clinical manifestations of secondary neutropenias, detailing their underlying causes and management, with a discussion of alternative and emerging therapeutic approaches.